Defluoridation of Water Using Aluminum Hydroxide Activated Carbon Biosorbents - Azmera Mezgebo Gebremariam; Abraha Gebrekidan Asgedom; Kebede Nigussie Mekonnen; Mengstu Etay Ashebir; Zenebe Hailu Gebremikael; Kassa Amare Mesfin (Advances in Materials Science and Engineering)
This study was aimed to investigate the efficiency of locally available low-cost and eco-friendly activated agricultural biosorbents produced from corncob and sorghum husk for the removal of fluoride from aqueous solution using batch adsorption. The activated biosorbents were characterized using SEM, XRD and FTIR spectroscopy. Effects of particle size (0.063–1.0 mm), contact time (15–120 min), pH (2–12), dose (2–10 g), and initial concentration (0.5–5.0 mg/L) were investigated. The morphology analysis revealed that biosorbents showed the presence of a high binding capacity for fluoride adsorption. The maximum adsorption was attained; size of the adsorbent 0.063 mm, pH 7, contact time 60 min, and 6 g dose of the biosorbents. Moreover, the adsorption kinetics followed the pseudo-second-order model and the adsorption isotherms fitted well to the Langmuir model. Furthermore, a field study was conducted using real water sample collected from Semema, Tigray, Ethiopia, and maximum fluoride removal was observed to be 79.44% and 77.05% for the activated carbons of Corncob and Sorghum husk at optimum conditions. Therefore, this experimental finding indicated that activated carbon of Corncob and Sorghum husk can be used as efficient, cheap, and eco-friendly biosorbents for the removal of fluoride from drinking water at community level.